The complexity of human performance variability on watch standing task. (September 2019) - Karwowski, Waldemar; Kern, David; Murata, Atsuo; Ahram, Tareq; Gutiérrez, Edgar; Sapkota, Nabin; Marek, Tadeusz
Abstract: The primary objective of this study was to examine the complexity of human temporal variability of topside roving watch task in naval operations concerning the reported times of ship status and to explore the potential presence of chaotic behavior and fractal properties of the reported log times. Topside rover reporting time intervals recorded in the deck logs of the USS Jason Dunham over the 2013–2015 period were analyzed to understand the underlying complexity of the watch standing task that is critical to the success of naval operations. The results on the 0–1 test, analysis of the largest Lyapunov exponents, as well the exploration of the fractal dimension and 1/f spectral analyses, showed that the fluctuation of standing watch time reports data exhibits chaotic and fractal system properties. The critical implications of the study findings for the human-centered design of complex systems were also discussed. Highlights: Applications of complexity theory will benefit future research in the field of ergonomics and human factors. The nonlinear systems dynamics approach to study human performance can be used to supplement statistical analysis. Human performance at work can exhibit chaotic and fractal behaviors that are not related to so-called "white" noise.